Emerging computation and information technologies for education : Proceeding of 2012 International Conference on Emerging Computation and Information teChnologies for Education (ECICE 2012) - Xu, Linli; Tian, Wenya; Mao, Elwin (Advances in Intelligent and Soft Computing, 2012)
The 2012 International Conference on Emerging Computation and Information teChnologies for Education (ECICE 2012) was  held on Jan. 15-16, 2012, Hangzhou, China.  The main results of the conference are presented in this proceedings book of carefully reviewed and accepted paper addressing the hottest issues in emerging computation and information technologies used for education. The volume covers a wide series of topics in the area, including Computer-Assisted Education, Educational Information Systems, Web-based Learning, etc.